Marital Fertility and Religion : Recent Changes in Spain - Alicia Adsera (Institute for the Study of Labor (IZA), 2004)
Since the onset of democracy in 1975, both total fertility and Mass attendance rates in Spain have dropped dramatically. I use the 1985 and 1999 Spanish Fertility Surveys to study whether the significance of religion in fertility behavior – both in family size and in the spacing of births – has changed. While in the 1985 SFS family size was similar among practicing and non-practicing Catholics, practicing Catholics portray significantly higher fertility during recent years. In the context of lower church participation, religiosity has acquired a more relevant meaning for demographic behavior. Among the youngest generation, non-practicing Catholics behave as those without affiliation. The small group of Protestants and Muslims has the highest fertility and interfaith unions are less fertile.
Keywords: Z21; J1; 330; fertility; religion; religiosity; Spain; timing of births; Fruchtbarkeit; Katholizismus; Religion; Schätzung; Spanien